Determination of oil composition of cowpea (Vigna unguiculata L.) seeds under influence of organic fertilizer forms - Yürürdurmaz Cengiz (Open Chemistry, 2022)
This research was carried out to determine the effects of different organic fertilizer forms on important quality elements of cowpea (Vigna unguiculata L.) seeds. The experiment was conducted according to the completely randomized blocks experimental design with three replications. In the experiment, palmitic acid (PALA), stearic acid (SA), and behenic acid (BA) from saturated fatty acids and palmitoleic acid (PLA), oleic acid (OA), linoleic acid (LA), and linolenic acid (LNA) ratios from unsaturated fatty acids were investigated. Besides these, quality factor such as oleic acid/linoleic acid (O/L) ratio, which is one of the oil stability values and iodine value (IV), unsaturated fatty acids/saturated fatty acids (USFA/SFA) ratio, and oil ratio and oil yield were investigated. As a result of these applications, the values of crude oil yield 27.08–40.68 kg ha−1 and some important quality properties of crude oil ratios 0.75–1.09%, PLA 0.250–0.372%, OA 12.00–22.85%, LA 22.97–29.97%, LNA 19.37–26.01%, PALA 19.53–23.53%, SA 5.27–7.04%, BA 1.86–2.37%, O/L acid ratio 0.402–1.043%, IV 113.73–136.76, and USFA/SFA ratio 2.08–2.74 were obtained.